Decomposing transverse momentum balance contributions for quenched jets in PbPb collisions at root s(NN)=2.76 TeV - (:unkn) unknown (SPRINGER, 2016)
Interactions between jets and the quark-gluon plasma produced in heavy ion collisions are studied via the angular distributions of summed charged-particle transverse momenta (p(T)) with respect to both the leading and subleading jet axes in high-p(T) dijet events. The contributions of charged particles in different momentum ranges to the overall event p(T) balance are decomposed into short-range jet peaks and a long-range azimuthal asymmetry in charged-particle p(T). The results for PbPb collisions are compared to those in pp collisions using data collected in 2011 and 2013, at collision energy root s(NN) = 2.76 TeV with integrated luminosities of 166 mu b(-1) and 5.3 pb(-1), respectively, by the CMS experiment at the LHC. Measurements are presented as functions of PbPb collision centrality, charged-particle p(T), relative azimuth, and radial distance from the jet axis for balanced and unbalanced dijets.
Keywords: Jet substructure; Heavy Ion Experiments; Heavy-ion collision; Quark gluon plasma